An applied study of digital retail - Bernini, Leonardo (2016)
In the past two decades the importance of the digital economy worldwide, retail in particular, has increased exponentially, in terms of value it generates and academic debate it spurs. The latter is represented by a vast and diverse body of knowledge which has been tested and applied to different degrees. Indeed, the study of underlying mechanisms that drive digital commerce is in continuous motion and many discussions are still in early stages of development. Such pieces of knowledge can only benefit from further examination. This dissertation sets out to provide additional insight into young fields of knowledge pertinent to digital retail. It does so by providing a business application to a selected body of notions; these concepts are tested against the CaffèLab business case whose revelatory and critical nature allows to corroborate, corroborate incrementally or contradict knowledge. Not only does this study corroborate most of the examined notions endowing them with a further business application; it surpasses its ‘applied business research’ nature by contributing: (1) novel knowledge to be added to the academic discussion such as the extension of the Technology Acceptance Model and the Combined Development Model and (2) recommendations to the analyzed company regarding its future courses of action.